Improvement of the stability of an electric double-layer transistor using a 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane barrier layer. (4th April 2019) - Liu, Yang; Fujii, Mami N; Ishida, Shoma; Ishikawa, Yasuaki; Miwa, Kazumoto; Ono, Shimpei; Bermundo, Juan Paolo Soria; Fujita, Naoyuki; Uraoka, Yukiharu
Abstract: Electric double-layer transistors (EDLTs) are capable of achieving ultra-high carrier density and very low operating voltages. However, chemical reactions cause structural change at the semiconductor–insulator interface resulting in unstable device operation and reduced device lifetime. In this work we propose a method of depositing a 1 H, 1 H, 2 H, 2 H -perfluorodecyltriethoxysilane (FDTS) layer which acts as a barrier between the semiconductor layer and the ionic liquid insulator. Our work shows that the effects of adding FDTS film are isolation of the chemical reaction and reduction of damage to the amorphous InGaZnO channel, thus achieving the effect of increasing device lifetime and stability.